Low yield metals and perforated steel shear walls for seismic protection of existing RC buildings. Issue 1 (1st January 2018) - Formisano, A.; Lombardi, L.
Abstract: In the field of the seismic protection of buildings, the use of steel plate shear walls (SPSWs) may be particularly profitable in the seismic retrofitting interventions of existing RC buildings designed for gravity loads only. Some past researches have shown that when traditional full SPSWs are used as bracing devices of framed buildings, they may induce excessive design forces to the surrounding frame members. Therefore, low yield steels (LYS) could be a valuable option to overcome this applicability limit. Nevertheless, the scarce availability on the market of these steels suggests the employment of aluminium alloys and perforated steel plates, which have the benefit of incurring excursions in plastic range already for low stress levels. In this paper, a parametric analysis concerning the use of perforated metal plate shear walls (MPSWs) for seismic upgrading of existing RC framed structures represents a novelty of the research in the retrofitting interventions field. To this purpose, first, some experimental tests have been considered to calibrate a finite element model of the panel devices by using the SeismoStruct software. Subsequently, the proposed FEM model has been used to design the retrofitting systems with either full MPSWs or perforated SPSWs of an existing RC residential five-storey building, designed between the 1960s and 1970s of the last century. Finally, the different retrofitting panel systems examined have been compared to each other in terms of both structural and economic viewpoints, allowing to select the best intervention strategy.